2019
DOI: 10.1021/acs.biomac.9b01355
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells (ADSCs) Loaded Gelatin-Sericin-Laminin Cryogels for Tissue Regeneration in Diabetic Wounds

Abstract: Healing in wounds like pressure ulcers, diabetic ulcers, venous ulcers, and arterial insufficiency ulcers is immensely hampered and causes both an economic burden and morbidity to patients. These wounds face a plethora of hostile conditions like elevated reactive oxygen species (ROS), impaired angiogenesis, senescent fibroblasts, and deficient stem cells that significantly diminish the probability of self-healing in these wounds. Adipose-derived stem cell therapy (ADSC) presents a promising approach to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…Tyeb et al designed a novel composite cryogels made of gelatin, sericin and laminin with applicability for the culture of fibroblasts, keratinocytes, ADSCs, and HUVEC cells [ 92 ]. Additionally, when the composite cryogels loaded with ADSCs were implanted in diabetic rats, these scaffolds showed enhanced wound healing capacity and mild inflammation [ 92 ]. Recently, GBCs have been investigated to imitate the microenvironment of different skin layers.…”
Section: Biomedical Applications Of Cbcs and Gbcsmentioning
confidence: 99%
“…Tyeb et al designed a novel composite cryogels made of gelatin, sericin and laminin with applicability for the culture of fibroblasts, keratinocytes, ADSCs, and HUVEC cells [ 92 ]. Additionally, when the composite cryogels loaded with ADSCs were implanted in diabetic rats, these scaffolds showed enhanced wound healing capacity and mild inflammation [ 92 ]. Recently, GBCs have been investigated to imitate the microenvironment of different skin layers.…”
Section: Biomedical Applications Of Cbcs and Gbcsmentioning
confidence: 99%
“…It is worth noting that angiogenesis was particularly enhanced when hADSCs were delivered through the BM side of XenoMEM™. Again, we believe that compositional differences may be responsible for this, considering that previous studies have shown improved angiogenetic capacity of scaffolds loaded with basement membrane components [59,60].…”
Section: Discussionmentioning
confidence: 87%
“…ADSCs are a type of pluripotent stem cells with high self-renewal ability with adipogenic, osteogenic, chondrogenic and myoblast differentiation [8]. Researches have proved that ADSCs have the ability to differentiate into hepatocytes with hepatocyte functions, such as glycogen synthesis, urea formation, expression of hepatocellular speci c genes, and cytochrome P450 enzyme activity, etc [9,10]. Current researches have testi ed that ADSCs can be applied to treat liver diseases such as hepatitis, liver brosis and liver failure [11][12][13].…”
Section: Introductionmentioning
confidence: 99%